Building Intergenerational Empathy to Overcome Stigma and Enhance Collaboration - Mustikasari, Anna Berliana; Defhany, Defhany (Jurnal Indonesia Sosial Sains, 2025)
Differences between generations are inevitable in social and organizational life. The mindset and communication style owned by the Baby Boomers, Generation X, Millennials, and Generation Z generations, often cause misunderstandings that can reduce productivity and hinder innovation, so an empathetic attitude is needed that can help connect communication and increase understanding between generations. This research shows that empathy can reduce negative stereotypes and support intergenerational collaboration. The method used is a literature study with a qualitative approach, which analyzes various sources related to empathy, intergenerational stigma, and intergenerational social dynamics. The results show that empathy can be strengthened through open dialogue, mentoring programs and collaborative activities, thereby increasing intergenerational understanding. Developing intergenerational empathy is essential to overcome stigma and create harmonious and productive social relationships.